A Critical Review of Properties and Analytical Methods for the Determination of Oxytetracyline in Biological and Pharmaceutical Matrices - Sversut, Rubia Adrieli [UNESP]; Silva, Adriane Andrade da; Mazon Cardoso, Teofilo Fernando; Kassab, Najla Mohamad; Amaral, Marcos Serrou do; Nunes Salgado, Herida Regina [UNESP] (Taylor & Francis Inc, 2017)
Antibiotics have an unquestionable importance in the treatment of many infections. Oxytetracycline is an antibiotic belonging to the class of tetracyclines, available for use in human and veterinary medicine. Development of analytical methods that prove the quality and efficacy of these drugs is fundamentally important to the pharmaceutical industry. In this context, the research presents an overview of the analytical profile of oxytetracycline, describing its chemical and pharmacological properties, and analytical methods for quantification of this drug in biological samples and pharmaceutical products. Oxytetracycline can be analyzed in these matrices by many types of methodologies. However, high-performance liquid chromatography is the most widely used, being recommended by official compendia. This kind of study can be useful to support the development of new efficient and sustainable analytical methods that may be utilized in the quality control routine of oxytetracycline in pharmaceutical products and pharmacokinetic monitoring in biological samples.
Keywords: Analytical methods; liquid chromatography; oxytetracycline; pharmacological properties; quality control